Impact of Corporate Governance on Firms’ Sustainability Performance: Case Study of BIST 50 Index Companies - Lehenchuk, Serhii; Zhyhlei, Iryna; Ivashko, Olena; Chulipa, Ihor; WIt, Bogdan (My University, 2024)
Purpose: the purpose of this study is to investigate whether corporate governance mechanisms and attributes influence the sustainability performance of companies included in the BIST 50 Index. Results and contributions: Regression analysis showed that there was a significant positive influence of board tenure on sustainability performance and all its types; board size on environmental performance; and a dummy variable for board evaluation externally facilitated and company size on sustainability, environmental, and social performance. A significant negative impact of director attendance at board meetings on social performance was also revealed. This study contributes to the literature on the role of corporate governance in achieving the SDGs for BIST 50 Index companies, highlighting the significant impact of its individual indicators on the achievement of sustainability performance. Methodology: The authors reviewed 45 sustainability reports of BIST 50 Index companies for 2023. Four indices—Sustainability Performance, Environmental Performance, Social Performance, and Corporate Governance Performance Indexes—were developed to characterize sustainability performance and its types based on a content analysis of sustainability disclosures. To analyze the influence of mechanisms and characteristics of the corporate governance system on sustainability performance, eight independent variables were used: board size, number of board meetings, director attendance at board meetings, board independence, board tenure, a dummy variable for board evaluation externally facilitated, a dummy variable for internal auditors present, and a dummy variable for CEO and Chair functions combined. Two control variables, company size and leverage, were used as well. Gap: Today, the scientific literature has no universal approach and understanding of how the corporate governance system should be developed to improve sustainability performance or its individual components. Relevance: Development of a corporate governance system is one of the ways to increase the level of sustainability performance of companies. Impact: The results of the study made it possible to produce several recommendations (expand the number of board members, develop an effective procedure for regular changes of general directors in company boards, introduce independent external control tools in the corporate governance systems of companies) that will lead to the achievement of SDGs 5, 8, 16.
Keywords: sustainable development goals; corporate governance; sustainability reporting; ESG reporting; institutional theory